Comparison of outcome after infrapopliteal angioplasty and pedal bypass surgery - Navickienė, Aušrinė; Builytė, Urtė; Kalinauskas, Gintaras (Lietuvos chirurgija, 2015)
Objective Percutaneous transluminal angioplasty (PTA) of crural arteries remains a valuable procedure for limb salvage in critical limb ischemia (CLI). Patients with anatomically unfavourable occlusive lesions of infrapopliteal arteries are usually offered a bypass surgery. The aims of this study were to report our experience, compare long-term results of surgical revascularization of pedal arteries and infrapopliteal PTA in patients with CLI, and assess the impact of diabetes mellitus and the type of treatment on limb salvage rates. Methods All tibial interventions to treat CLI, which were performed during the period of January 1999 to December 2013, were retrospectively analysed. The outcomes of tibial PTA procedures and open surgery – bypasses to dorsal pedal artery (DP) – were compared. The impact of diabetes mellitus control on the primary revascularization procedures’ outcomes was analysed. Results Three patient groups were formed: the open repair group (treated by dorsal pedal artery bypass operation) – 193 patients, the endovascular repair group – 103 limbs in 98 patients, and the combined treatment group (endovascular repair and dorsal pedal artery bypass) – 84 patients. The cumulative patency rate in the open repair group at a 1-year period was 47.5%, in the endovascular repair group – 6.9% and in the combined treatment group – 79.6%. The best results of revascularization were achieved in the combined treatment group (p < 0.007). The limb salvage rate at the 1-year follow-up was 84.1% in the open repair group, 35.4% in the endovascular repair group, and 83.1% in the combined treatment group. In the combined treatment group, limbs were saved for a longer period (p < 0.01). The patency rates for DP artery bypasses at the 1-year follow-up in diabetic patients were 60.4%, in non-diabetic patients – 21.8% (p = 0.013), and for PTA procedures in diabetic patients – 3.6%, in non-diabetic – 10.1%. The patency rate in patients under tight plasma glucose control was 55.2%, in uncontrolled diabetes group – 43.6% after two years. The limb salvage rate in patients under a tight plasma glucose control was 79.31%, in uncontrolled diabetes group – 61.82% after two years. These findings had no significance (p > 0.05). Conclusion Both infrapopliteal angioplasty and bypass surgery provide an acceptable limb salvage rate, but the follow-up patency appears to be better after bypass surgery. The duration of revascularization in the open repair group was longer as compared to the endovascular repair group. The best revascularization results were in diabetic patients after open surgery combined with PTA (combined treatment group). DP artery bypass is a safe and durable procedure in patients with CLI and patients with diabetes mellitus. Tight plasma glucose levels control has no effect on primary revascularization outcomes.